Mycophenolate Mofetil Attenuates DOCA-Salt Hypertension: Effects on Vascular Tone - Moes, Arthur D.; Severs, David; Verdonk, Koen; van der Lubbe, Nils; Zietse, Robert; Danser, A. H. J.; Hoorn, Ewout J. (Frontiers in Physiology, 2018)
Inflammation is increasingly recognized as a driver of hypertension. Both genetic and pharmacological inhibition of B and T cells attenuates most forms of experimental hypertension. Accordingly, the immunosuppressive drug mycophenolate mofetil (MMF) reduces blood pressure in the deoxycorticosterone acetate (DOCA) salt model. However, the mechanisms by which MMF prevent hypertension in the DOCA-salt model remain unclear. Recent studies indicate that immunosuppression can inhibit sodium transporter activity in the kidney, but its effect on vascular tone is not well characterized. Therefore, the aim of the present study was to analyze the vascular and renal tubular effects of MMF in the DOCA-salt model in rats (4 weeks without uninephrectomy). Co-treatment with MMF attenuated the rise in blood pressure from day 11 onwards resulting in a significantly lower telemetric mean arterial pressure after 4 weeks of treatment (108 ± 7 vs. 130 ± 9 mmHg, P < 0.001 by two-way ANOVA). MMF significantly reduced the number of CD3+ cells in kidney cortex and inner medulla, but not in outer medulla. In addition, MMF significantly reduced urinary interferon-γ excretion. Vascular tone was studied ex vivo using wire myographs. An angiotensin II type 2 (AT2) receptor antagonist blocked the effects of angiotensin II only in the vehicle group. Conversely, L-NAME significantly increased the angiotensin II response only in the MMF group. An endothelin A receptor blocker prevented vasoconstriction by endothelin-1 in the MMF but not in the vehicle-group. MMF did not reduce the abundances of the kidney sodium transporters NHE3, NKCC2, NCC or ENaC. Together, our ex vivo results suggest that DOCA-salt induces AT2 receptor-mediated vasoconstriction. MMF prevents this response and increases nitric oxide availability. These data provide insight in the antihypertensive mechanism of MMF and the role of inflammation in dysregulating vascular tone.